2014
DOI: 10.1007/s00424-014-1502-6
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids produced upon action potential firing evoke a Cl− current via type-2 cannabinoid receptors in the medial prefrontal cortex

Abstract: The functional presence of type-2 cannabinoid receptors (CB2Rs) in layer II/III pyramidal neurons of the rat medial prefrontal cortex (mPFC) was recently demonstrated. In the present study, we show that the application of the endocannabinoids (eCBs) 2-arachidonoylglycerol (2-AG) and methanandamide [a stable analog of the eCB anandamide (AEA)] can activate CB2Rs of mPFC layer II/III pyramidal neurons, which subsequently induces a Cl(-) current. In addition, we show that action potential (AP) firing evoked by 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Extensive research over the past decade indicates that functional CB 2 Rs are expressed in glial cells and neurons in the brain [1,43,44], and evidence from qRT-PCR and ISH assays in our present study and previous reports strongly support this expression [9,26,28]. Electrophysiological evidence of brain CB 2 R modulation of neuronal activity in the cortex [31][32][33], hippocampus [22,25,30], striatum [29], and midbrain [9,26] further support the presence of functional CB 2 Rs in the brain. We recently reported that systemic or local administration of the selective CB 2 R agonist JWH133 or GW405833 into the nucleus accumbens significantly inhibited DA release in this region and attenuated intravenous cocaine self-administration, cocaine-enhanced locomotion, and cocaine-enhanced extracellular DA in the nucleus accumbens.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Extensive research over the past decade indicates that functional CB 2 Rs are expressed in glial cells and neurons in the brain [1,43,44], and evidence from qRT-PCR and ISH assays in our present study and previous reports strongly support this expression [9,26,28]. Electrophysiological evidence of brain CB 2 R modulation of neuronal activity in the cortex [31][32][33], hippocampus [22,25,30], striatum [29], and midbrain [9,26] further support the presence of functional CB 2 Rs in the brain. We recently reported that systemic or local administration of the selective CB 2 R agonist JWH133 or GW405833 into the nucleus accumbens significantly inhibited DA release in this region and attenuated intravenous cocaine self-administration, cocaine-enhanced locomotion, and cocaine-enhanced extracellular DA in the nucleus accumbens.…”
Section: Discussionsupporting
confidence: 85%
“…In situ hybridization (ISH) assays revealed CB 2 R mRNA expression in several neuronal phenotypes, including glutamatergic neurons in the cortex and hippocampus [22,24,25] and dopaminergic (DA) neurons in the midbrain [9,[26][27][28][29]. Electrophysiological assays confirmed the presence of functional CB 2 Rs in brain glutamatergic neurons [22,[30][31][32], GABAergic neurons [33], and DA neurons [9,22,26,29]. However, the specificity of the detected CB 2 R signals was questioned because CB 2 -knockout (CB 2 -KO) mice were not used as controls in many early studies [34].…”
Section: Introductionmentioning
confidence: 99%
“…However in brain slice experiments, mimicking CB-R-mediated synaptic plasticity induced by endogenous 2-AG requires 10–30 μM exogenous 2-AG (e.g. Bacci et al, 2004; den Boon et al, 2014; Marinelli et al, 2008 and 2009; Wilson and Nicoll, 2001). This discrepancy is likely due to the difficulty of applying such hydrophobic compounds that readily partition non-specifically into membranes on the entire brain slice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in some neurons, production of 2-AG reduces excitability in an autocrine manner, mediated by CB receptors in the postsynaptic membrane (Bacci et al, 2004; den Boon et al, 2014; Marinelli et al, 2008; 2009; Stempel et al, 2016). Our study utilized three, separate G q/11 receptors known to produce 2-AG-dependent effects on synaptic plasticity in dopamine neurons and the results demonstrate that endogenously mobilizing 2-AG reduced I A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation